Experimental assessment of the behavior of prefabricated concrete elements (horizontal tiles and columns), under the application of perpendicular loads to the wall plane - Villalobos Ramírez, Francisco (2025)
In this research it was studied the prefabricated system of columns and horizontal tiles with uniformly distributed loads perpendicular to the plane of the wall. For this, a wall on natural scale was built, It was made by two groups of tiles, top plate beam and concrete foundation. The load was applied with air bags to generate a uniform pressure on the wall. The most important result is the experimental verification that the columns are the critical design element in prefabricate system of columns and horizontal tiles. It was also possible to demonstrate that the resistant requirements stablished in INTE C131:2019 are adequate for support wind and earthquake pressure safely.